The Use of Substitution as A Grammatical Cohesive Device in A book of Map of The Soul7 dalam Dunia BTS - Anggraini, Melina; Sumarlam, Sumarlam (Reduplikasi: Jurnal Penelitian Pendidikan Bahasa Indonesia, 2024)
This study investigates the use of substitution markers in the book Map of the Soul: 7 in BTS World, focusing on four main topics: Pendahuluan, Persona, Shadow, and Ego. Employing a qualitative descriptive method, the research identifies and categorizes substitution markers into nominal, verbal, phrasal, and clausal types. Key findings reveal 14 substitution markers in the Introduction (5 nominal, 3 verbal, 44 phrasal, and 7 clausal), 81 in the Persona chapter (27 nominal, 2 phrasal, and 6 clausal), 43 in the Shadow chapter (3 nominal, 34 phrasal, and 6 clausal), and 28 in the Ego chapter (11 nominal and 17 phrasal). The findings indicate limited verbal substitution, and use of phrasal substation frequently. This research discover variation of substutional level and chained substitution. This research enhances the understanding of grammatical cohesion in literature, particularly in narratives for young readers, by emphasizing the importance of substitution in maintaining textual unity and engagement.Keywords: cohesion, substitution, mots:7